2015
DOI: 10.1056/nejmoa1407417
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of an Aerosolized Vaccine against Measles

Abstract: BACKGROUNDAerosolized vaccine can be used as a needle-free method of immunization against measles, a disease that remains a major cause of illness and death. Data on the immunogenicity of aerosolized vaccine against measles in children are inconsistent. METHODSWe conducted an open-label noninferiority trial involving children 9.0 to 11.9 months of age in India who were eligible to receive a first dose of measles vaccine. Children were randomly assigned to receive a single dose of vaccine by means of either aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 21 publications
0
55
1
Order By: Relevance
“…Therefore, there has been considerable interest in evaluating different routes of administration. A recent clinical trial found that seroconversion rates were 10% lower for the aerosolized measles vaccine than for the conventional injected vaccine [83, 84]. However, the measles vaccine administered via microneedle patch has shown promise in non-human primate studies [85].…”
Section: New Technologies and Approaches For Studying Immune Respomentioning
confidence: 99%
“…Therefore, there has been considerable interest in evaluating different routes of administration. A recent clinical trial found that seroconversion rates were 10% lower for the aerosolized measles vaccine than for the conventional injected vaccine [83, 84]. However, the measles vaccine administered via microneedle patch has shown promise in non-human primate studies [85].…”
Section: New Technologies and Approaches For Studying Immune Respomentioning
confidence: 99%
“…In addition to the cost advantages, microneedle patches potentially have several important logistical advantages (e.g., reduced cold chain requirements, fewer trained staff required) that could increase vaccine coverage, especially in hard-to-reach communities. Other vaccine-related technologies, such as aerosolized vaccines, could also offer advantages over the subcutaneous vaccination [19]. These technologies should also be carefully monitored and evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Whether LAIVs will have much enhanced protective efficacy if deliberately delivered to the LRT requires thorough investigation to determine whether this is more efficient in inducing both homologous and heterologous protection against SI in pigs. However, despite major advances in aerosol vaccine delivery in humans [53] and some examples of local delivery to livestock, no practical devices for aerosol delivery are yet available for farm animals in the field.…”
Section: Live Attenuated Influenza Vaccinesmentioning
confidence: 99%